Sastra dan agama : tinjauan kesusastraan Indonesia modern bercorak Islam - Saridjo, Marwan (Jakarta, Indonesia : Yayasan Ngali Aksara dan Penamadani, 2006)
Islamic aspects in modern Indonesian literature
Includes bibliographical references (p. 299-307) and index
Keywords: Indonesian literature -- 20th century -- Islamic influences; Indonesian literature -- Islamic influences